Colour polymorphism in a leafhopper species Macropsis notata (Prohaska, 1923) (Hemiptera: Cicadellidae: Macropsinae) with new synonyms - Li, Hu; Tishechkin, Dmitri Yu.; Dai, Renhuai; Li, Zizhong (Zootaxa, 2012)
Colour polymorphism in a leafhopper species Macropsis notata (Prohaska, 1923) is investigated based on large quantitiesof materials from China, eight colour forms are recognized. The following new synonymies are proposed: M. salicis Li, 1989 syn. nov. and M. matsudanis Wei & Cai, 1998 syn. nov. of M. notata (Prohaska, 1923).